2019
DOI: 10.1002/ijfe.1773
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy spillovers in emerging economies

Abstract: This paper explores for spillovers from monetary policy in the United States to a number of emerging market economies. We estimate the Elder and Serletis (2010) bivariate structural GARCH-in-Mean VAR in the U.S. monetary policy rate and the policy rate of each of six emerging economies that target the in ‡ation rate -Brazil, Chile, Mexico, Romania, Serbia, and South Africa. We also estimate the same model in the U.S. monetary policy rate and the exchange rate (against the U.S. dollar) of each of six emerging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…Although the reactions of domestic currencies were similar for advanced economies versus emerging markets during the pre-COVID-19 period, they were higher for advanced economies during the COVID-19 period. This result is also consistent with earlier studies (Georgiadis, 2016 ; Albagli et al, 2019 ; Azad & Serletis, 2020 ) which showed evidence for heterogeneity across countries regarding the spillover effects of U.S. monetary policy.…”
Section: Estimation Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Although the reactions of domestic currencies were similar for advanced economies versus emerging markets during the pre-COVID-19 period, they were higher for advanced economies during the COVID-19 period. This result is also consistent with earlier studies (Georgiadis, 2016 ; Albagli et al, 2019 ; Azad & Serletis, 2020 ) which showed evidence for heterogeneity across countries regarding the spillover effects of U.S. monetary policy.…”
Section: Estimation Resultssupporting
confidence: 93%
“…Regarding the spillover effects of U.S. monetary policy, domestic exchange rates (constructed as appreciation of currencies) increased for almost all countries during the pre-COVID-19 period represented by the year of 2019, except for Brazil, India, and Turkey for which the credible intervals included insignificant effects on exchange rates after one year. These results suggesting that there is evidence for the spillover effects of U.S. monetary policy are consistent with earlier studies (e.g., Maćkowiak, 2007 ; Georgiadis, 2016 ; Chen et al, 2016 ; Ho et al, 2018 ; Hanisch, 2019 ; Albagli et al, 2019 ; Azad & Serletis, 2020 ). Based on the discussion in the theoretical motivation section, it was implied that exchange rates of several countries appreciated through financial arbitrage opportunities (capital inflows) following an unexpected U.S. monetary loosening during the pre-COVID-19 period, except for certain countries with potential higher financial risk perceptions in 2019.…”
Section: Estimation Resultssupporting
confidence: 92%
See 1 more Smart Citation